2007
DOI: 10.1074/jbc.m700133200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Cannabinoids That Induce Cell Death through Mitochondrial Permeability Transition in Cannabis Leaf Cells

Abstract: Cannabinoids are secondary metabolites stored in capitatesessile glands on leaves of Cannabis sativa. We discovered that cell death is induced in the leaf tissues exposed to cannabinoid resin secreted from the glands, and identified cannabichromenic acid (CBCA) and ⌬ 1 -tetrahydrocannabinolic acid (THCA) as unique cell death mediators from the resin. These cannabinoids effectively induced cell death in the leaf cells or suspension-cultured cells of C. sativa, whereas pretreatment with the mitochondrial permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 46 publications
3
62
0
1
Order By: Relevance
“…In H. perforatum plants the phototoxin hypericin accumulats in secretory glands on leaves and flowers (Fields et al, 1990;Zobayed et al, 2006). It has been confirmed that cannabinoids are cytotoxic compounds and thus they should be biosynthesized and accumulated in highly specialized cells such as glandular trichomes (Morimoto et al, 2007).…”
Section: Effect Of Elicitors On Cannabinoid Biosynthesis From C Satimentioning
confidence: 98%
“…In H. perforatum plants the phototoxin hypericin accumulats in secretory glands on leaves and flowers (Fields et al, 1990;Zobayed et al, 2006). It has been confirmed that cannabinoids are cytotoxic compounds and thus they should be biosynthesized and accumulated in highly specialized cells such as glandular trichomes (Morimoto et al, 2007).…”
Section: Effect Of Elicitors On Cannabinoid Biosynthesis From C Satimentioning
confidence: 98%
“…The THCA synthase reaction produces hydrogen peroxide as well as THCA during the oxidation of Taura et al (1996) trans-CBGA CBGA (Sirikantaramas et al 2004); a toxic amount of hydrogen peroxide could be accumulated together with the cannabinoids which must be secreted into the storage cavity from the glandular hairs to avoid cellular damage itself. Additionally, Morimoto et al (2007) have shown that cannabinoids have the ability to induce cell death through mitochondrial permeability transition in cannabis leaf cells, suggesting a regulatory role in cell death as well as in the defense systems of cannabis leaves. On the other hand, although CBN type cannabinoids have been isolated from cannabis extracts, they are probably artifacts.…”
Section: Cannabinoid Biosynthesismentioning
confidence: 98%
“…Various theories, all relating to the defence against biotic and abiotic stress (Pate 1998), attribute ecological benefits to the presence of cannabinoids which would explain the rarity of the knockout allele. Recently, Morimoto et al (2007) reported on the ability of cannabinoids to induce necrotic cell death in the Cannabis leaf cells. They suggested that these compounds play a role in the plant's defence system and in the process of leaf senescence.…”
Section: Ecological and Evolutionary Implicationsmentioning
confidence: 99%